The Solitary Bees : Biology, Evolution, Conservation - Danforth, Bryan N.; Minckley, Robert L.; Neff, John L. (Princeton University Press, 2019)
The most up-to-date and authoritative resource on the biology and evolution of solitary beesWhile social bees such as honey bees and bumble bees are familiar to most people, they comprise less than 10 percent of all bee species in the world. The vast majority of bees lead solitary lives, surviving without the help of a hive and using their own resources to fend off danger and protect their offspring. This book draws on new research to provide a comprehensive and authoritative overview of solitary bee biology, offering an unparalleled look at these remarkable insects.The Solitary Bees uses a modern phylogenetic framework to shed new light on the life histories and evolution of solitary bees. It explains the foraging behavior of solitary bees, their development, and competitive mating tactics. The book describes how they construct complex nests using an amazing variety of substrates and materials, and how solitary bees have co-opted beneficial mites, nematodes, and fungi to provide safe environments for their brood. It looks at how they have evolved intimate partnerships with flowering plants and examines their associations with predators, parasites, microbes, and other bees. This up-to-date synthesis of solitary bee biology is an essential resource for students and researchers, one that paves the way for future scholarship on the subject.Beautifully illustrated throughout, The Solitary Bees also documents the critical role solitary bees play as crop pollinators, and raises awareness of the dire threats they face, from habitat loss and climate change to pesticides, pathogens, parasites, and invasive species.